Role of tax security in organization economic security system - E. L. Gulkova; M. V. Karp; M. V. Tipalina (Вестник университета)
The article studies problematic issues of tax security as a part of the organization’s economic security. Successful operation of a company depends on tax compliance, correct definition of the tax function, and timely identification of tax risks. The purpose of the research is to justify the role of tax security as one of the key parts of the organization’s economic security. The approaches to minimizing the tax risks of companies have been analyzed. The arbitration practice, letters from the Federal Tax Service of Russia, and various interactive services that allow taxpayers to conduct economic analysis have been reviewed. The main problems that may arise for organizations in building the tax security system have been highlighted and the possible ways of solving it defined. The article concludes that it is necessary to approve the organization’s tax risk of management regulations and comprehensive diagnostics of the internal tax control system for the taxpayers who do not apply tax monitoring. The results obtained can be used in the formation of regulations on the organization’s tax planning, improving the provisions of the orders of the Federal Tax Service of Russia on the requirements for organization of internal tax control system for the taxpayers who do not apply tax monitoring.